Ecosystem impact and dietary exposure of polychlorinated biphenyls (PCBs) and heavy metals in Chinese mitten crabs (Eriocheir sinensis) and their farming areas in Jiangsu, China - Hanxiaoya Zhang (Elsevier, 2021)
This study investigated the presence of 18 dioxin-like and non-dioxin-like polychlorinated biphenyls (dl- and ndl-PCBs), heavy metals (Cd, Hg, Pb, and As) in Chinese mitten crabs (Eriocheir sinensis) and their distribution in Jiangsu, China. Risk assessment and source apportionment were employed for evaluating the eco-toxicological impact and human exposure. It was found that the compositions of PCBs varied spatially, suggesting different sources of pollutants, whilst PCB 28, 105, 114, and 126 were consistently found in all sample types, suggesting a common pollution source remained, and the bio-accumulation process was in effect. The total PCBs in sediment were found much higher than in water, and brown meat had the highest and most diverse PCB congeners among all tissues. The presence of heavy metals was found in all samples in descending order of As>Cd>Pb>Hg and in the order of shell>brown meat>white meat>gill for crabs. The results of risk assessment indicated that the potential carcinogenic and non-carcinogenic risks were within the acceptable range for long-term consumption of the crabs overall. However, the highest toxic equivalent (TEQ), carcinogenic, and non-carcinogenic risks were all recorded in Location C, where dl-PCB 126, 169, and As contributed to the majority of the risks. The ecological risk posed by all HMs was low, but cases of serious point source pollution have been found in the investigated regions, and risks caused by Cd individually should raise concerns. Source apportionment study revealed that the contaminants mostly originated from anthropogenic activities. Natural deposition and transportation played an important role as well.